2014
DOI: 10.1371/journal.pone.0105778
|View full text |Cite
|
Sign up to set email alerts
|

Rose Bengal Acetate PhotoDynamic Therapy (RBAc-PDT) Induces Exposure and Release of Damage-Associated Molecular Patterns (DAMPs) in Human HeLa Cells

Abstract: The new concept of Immunogenic Cell Death (ICD), associated with Damage Associated Molecular Patterns (DAMPs) exposure and/or release, is recently becoming very appealing in cancer treatment. In this context, PhotoDynamic Therapy (PDT) can give rise to ICD and to immune response upon dead cells removal. The list of PhotoSensitizers (PSs) able to induce ICD is still short and includes Photofrin, Hypericin, Foscan and 5-ALA. The goal of the present work was to investigate if Rose Bengal Acetate (RBAc), a powerfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 45 publications
6
66
0
Order By: Relevance
“…These data are consistent with the observation that HMGB1 was passively released from photosensitized HeLa cells treated with a rose bengal analog [39]. Pretreatment with rose bengal acetate led to apoptosis and autophagy and the secretion of HSP70, HSP90 and HMGB1.…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with the observation that HMGB1 was passively released from photosensitized HeLa cells treated with a rose bengal analog [39]. Pretreatment with rose bengal acetate led to apoptosis and autophagy and the secretion of HSP70, HSP90 and HMGB1.…”
Section: Discussionsupporting
confidence: 91%
“…[47][48][49] For example, PDT with Photofrin, Hypericin, and Rose Bengal acetate has been shown to trigger the expression of CRT on the tumor cell surface in vitro. 8,50,51 The present study demonstrated that BAM-SiPc-PDT could induce the expression of surface CRT on CT26 tumor cells, together with two other DAMPs, HSP70, and HSP90, in vitro (Figure 1b and c). These surface-exposed HSPs have been reported to augment anti-tumor immunity by assisting DCs in acquiring and presenting tumor-derived antigens.…”
Section: Discussionsupporting
confidence: 52%
“…The introduction of heavy atoms into the rings, such as the halogen atoms bromine and iodine, increases the triplet yield of the molecule by facilitating intersystem crossing. Rose Bengal has a long history as a photoactive dye and has been explored for antimicrobial applications [44], tissue bonding applications [45] and anti-cancer applications [46]. …”
Section: Synthetic Dyesmentioning
confidence: 99%